MAHASISWA MENJAWAB TANTANGAN ZAMAN - Nurhadi Nurhadi (Universitas Bina Sarana Informatika, 2011)
Candradimuka mean is Candradimuka Crater, where the son of the milky tetuka forget andgalvanijed into a mighty gathutkaca. That proverbial student crater candra dimuka placeslikeindonesia and process of studen to become leaders of idonesia. this organization such as thecandradimuka while cadres like ghatutkaca.That imageis symbolic when in face, the cadres of the muslim students association as larfanpane,ahmad tirtosudiro,dahlan ranumiharja, sulastomo, marie muh ammad, jusuf kalla, aniswati, akbartanjung, urbaningrum annas and others displays the important things, and developmentorganizationdoctrine of struggle students recruitmen muslim student association studentdevelopmen student association, fascination student prospect ahead for student organization andstudents view of islam figures. Equippmen with the five doctrines of islamic thought indonesiamemory explanation on islam, sunnahand the prophet tafseer purpose, tafser indepence studentassociation,and the NDP (core value struggle). Character development of the nation’s first, bothmake the country focus on its national interests and make the nation’s third century chalengestfacing indonesia compatible 21 sustained competitive advantage by mastering sciebce andtechnologi and qualivied humand resources. Student association took step sconsolidate theorganization and insight as follows: streghthen the base (back to campust), rather than anideological paradigma profesionalism, consolidation, increase performance. In an effort toconsolidate and raise the image of student is carry out activities such as character development ofthe nation throught recruitmen improve the quality of human resources with themastery of scienceand technoligi and others. Student association is very noble goal, about to realize the human ideal.Is the ideal goal of human beings who have a 5 kualita with 17 indicators. Establish a cadre of airstudents association of the faith, air science,and air amal according to the mandate.Keywords: state administration, student asociation, nationalism, democratization, primordialism,arts, civil society